Incidence of Intracranial Hemorrhage and Outcomes after Ground-level Falls in Geriatric Trauma Patients Taking Preinjury Anticoagulants and Antiplatelet Agents. Issue 10 (October 2014) - Reddy, Subhash; Sharma, Rohit; Grotts, Jonathan; Ferrigno, Lisa; Kaminski, Stephen
Antiplatelet and anticoagulant medication increases the risk of intracranial hemorrhage (ICH) after a fall in geriatric patients. We sought to determine whether there were differences in ICH rates and outcomes based on type of anticoagulant or antiplatelet agent after a ground-level fall (GLF). Our institutional trauma registry was used to identify patients 65 years old or older after a GLF while taking warfarin, clopidogrel, or aspirin over a 2-year period. Rates and types of ICH and patient outcomes were evaluated. Of 562 patients who met inclusion and exclusion criteria, 218 (38.8%) were on warfarin, 95 (16.9%) were on clopidogrel, and 249 (44.3%) were on aspirin. Overall ICH frequency was 15 per cent with no difference in ICH rate, type of ICH, need for craniotomy, mortality, or intensive care unit or hospital length of stay between groups. Patients with ICH were more likely to present with abnormal Glasgow Coma Score, history of hypertension, and/or loss of consciousness.